A novel numerical simulation study on the flow mechanisms of deep low-permeability gas reservoirs - Ruidong Wu; Chunguang Zhang; Rui Wang; Qinghao Sun; Gangxiang Song; Meixue Shi (Journal of Petroleum Exploration and Production Technology)
Abstract Due to the high pressure and low permeability, gas reservoirs in the East China Sea show significant reservoir stress sensitivity, non-linear flow characteristics. Meanwhile, relative permeabilities may change during the development. Conventional numerical simulation methods fails to characterize the impact of these complex flow mechanisms on the production. To this end, we quantitatively evaluate their influences and established a mathematical flow model of deep high-pressure low-permeability gas reservoirs. The mathematical model was discretized and linearized to obtain fully implicit solutions for pressure and saturation. The pre- and post-processing modules of the simulator were integrated with ECLIPSE. Based on parameter sensitivity analysis, the impact of these special flow mechanisms of deep low-permeability gas reservoirs on production were clarified through testing of the simulator. This novel model was applied in the S gas field in the East China Sea. The results showed that the stress sensitivity and differential pressure between the BHP and FP determined the stable production period and recovery. The BHP and the scope of the pressure decline decreased due to the non-linear flow behavior. Variations in gas-water relative permeabilities during the depletion lead to an increase in water production and a reduction in stable production period. The numerical simulation method improves the accuracy of production history match for low-permeability gas reservoirs, and agrees well with the real cases, providing a guidance for field development plans.